Pemilu Tanpa Pelanggaran: Asas Netralitas Demi Mewujudkan ASN Berintegritas: Elections Without Violations: The Principle of Neutrality Realizes Civil Servants with Integrity - nurul kamaly (Puslatbang KHAN, 2023)
Neutrality is a crucial aspect of elections that has an important role in ensuring that the election process is carried out fairly, transparently, and openly for all election participants. Neutral elections can also ensure that every voter's vote is counted accurately and provide equal opportunities for all participants to compete fairly in elections. Many demands were made by the community for the creation of civil servants who were neutral and did not side with anyone in practical politics. Field facts have proven that in the 2019 election alone there were 1536 alleged violations of the neutrality of civil servants with a division of 914 alleged violations in elections and around 1398 in regional elections. This article is prepared using a qualitative approach. Qualitative study method is a method that seeks to produce information in the form of records and data that are descriptive in research, In the data collection technique, this research uses literature studies or library research, namely by using primary sources in the form of reading materials such as books, journals, documents, official websites, and other literature. As a matter of comparison in the application of the principle of neutrality, regulations in Singapore have limited the relationship between civil servants and political officials aimed at minimizing violations of the Code of Conduct for Ministers of 2005.